Collision and contact sport participation and quality of life among adolescent athletes - Howell, D. R.; Kirkwood, M. W.; Laker, S.; Wilson, J. C. (Journal of Athletic Training, 2020)
Context: Researchers investigating collision and contact sport participation during high school have found mixed results. Understanding the association between current contact and collision sport participation and quality-of-life outcomes can enhance our knowledge about the risks and benefits of sport participation. Objective: To examine quality-of-life outcomes among high school athletes who reported participation in collision and contact sports in the year preceding assessment compared with no- or limited-contact sport athletes. Design: Cross-sectional study. Setting: Preparticipation physical examination. Patients or Other Participants: High school athletes 13 to 18 years of age. Main Outcome Measure(s): We obtained sport participation and Patient-Reported Outcomes Measurement Information System (PROMIS) Pediatric-25 outcomes, which assess self-reported, quality-of-life domains in the preceding 7 days (ie, state assessment). Our grouping variable was collision and contact versus no- or limited-contact sport participation during the year preceding assessment. We used multivariable linear regression models to identify the associations between PROMIS scores and collision and contact sport participation and adjusted for sex; age; history of bone, muscle, ligament, or tendon injury; history of acute fracture or dislocation; and history of concussion. Results: A total of 143 (51%) athletes reported collision and contact sport participation (24% female, mean age = 15.1 ± 1.7 years) and 138 (49%) reported no- or limited-contact sport participation (66% female, mean age = 15.4 ± 1.2 years). A higher proportion of collision and contact sport athletes reported a history of time loss for bone, muscle, ligament, and tendon injuries (51% versus 29%, P < .001) and for acute fracture or dislocation (46% versus 26%, P < .001) than did no- or limited-contact athletes. After adjusting for covariates, we found that collision and contact sport participation was significantly associated with lower state anxiety (ß = -1.072, 95% confidence interval = -1.834, -0.310, P = .006) and depressive (ß = -0.807, 95% confidence interval = -1.484, -0.130, P = .020) symptom scores. Conclusions: Collision and contact sport athletes reported fewer anxiety and depressive symptoms in the week preceding evaluation than did no- or limited-contact sport athletes, but they had more extensive orthopaedic injury histories. Potential benefits and risks are associated with collision and contact sport participation. These data reinforce the need to examine the assumption that youth collision and contact sports are associated with negative quality of life.